Microvessel stenosis, enlarged perivascular spaces, and fibrinogen deposition are associated with ischemic periventricular white matter hyperintensities. (19th September 2021) - Roseborough, Austyn D.; Rasheed, Berk; Jung, Youngkyung; Nishimura, Kevin; Pinsky, William; Langdon, Kristopher D.; Hammond, Robert; Pasternak, Stephen H.; Khan, Ali R.; Whitehead, Shawn N.
Abstract: Periventricular white matter hyperintensities (pvWMH) are neuroimaging abnormalities surrounding the lateral ventricles that are apparent on magnetic resonance imaging (MRI). They are associated with age, neurodegenerative disease, and cerebrovascular risk factors. While pvWMH ultimately represent a loss of white matter structural integrity, the pathological causes are heterogeneous in nature, and currently, cannot be distinguished using neuroimaging alone. pvWMH could occur because of a combination of small vessel disease (SVD), ependymal loss, blood–brain barrier dysfunction, and microgliosis. In this study we aimed to characterize microvascular stenosis, fibrinogen extravasation, and microgliosis within pvWMH with and without imaging evidence of periventricular infarction. Using postmortem neuroimaging of human brains ( n  = 20), we identified pvWMH with and without periventricular infarcts (PVI). We performed histological analysis of microvessel stenosis, perivascular spaces, microgliosis, and immunohistochemistry against fibrinogen as a measure of serum protein extravasation. Herein, we report distinctions between pvWMH with and without periventricular infarcts based on associations with microvessel stenosis, enlarged perivascular spaces, and fibrinogen IHC. Microvessel stenosis was significantly associated with PVI and with cellular deposition of fibrinogen in the white matter. The presence of fibrinogen was associated with PVI and increased number of microglia. These findings suggest that neuroimaging‐based detection of infarction within pvWMH may help distinguish more severe lesions, associated with underlying microvascular disease and BBB dysfunction, from milder pvWMH that are a highly frequent finding on MRI. Abstract : White matter fibrinogen deposition is associated with post‐mortem MRI evidence of periventricular infarcts, arteriole stenosis and increases in microglia.